Teaching Writing By Using Diamante Poetry - Desi Andriani (Lesson Journal: Languange, Applied Linguistics, and Education Journal, 2021)
This paper describes activities in teaching writing by using literature. The literature is diamante poetry. The purposes of this article are the first provide a theoritical discussion about writing sentence after students conduct a poem and provide a sample of lesson plan for teaching writing sentence by using diamante poetry at Elementary School. Teachers can use diamante poetry strategy to make students be able to write sentence. Because writing is important skill and should be taught from the beginning.